INTRODUCTION OF EXPLANTS AND REPRODUCTION ON NUTRIENT MEDIUM OF DONOR MATERIAL IN VITRO VARIETIES OF CALLISTEPHUS CHINENSIS (L.) NESS. FOR ITS FURTHER USE IN LANDSCAPING - Polishchuk V.V.; Turchina S.Ya.; Balabak A.F.; Kozachenko I.V.; Mamchur V.V.; Karpuk L.M.; Polishchuk T.V. (Scientific Journal of Pedagogy and Economics, 2020)
On the recent methods of biotechnology are increasingly used in plant breeding and seed production. Herbaceous plants such as strawberries, potatoes, a vegetable, some medicinal and others are capable of vegetative propagation the traditional methods of culture, successfully introduced in both in vitro and can achieve a high rate of reproduction. Modern plant biotechnology – the sum of the technologies developed in molecular and cell biology of plants – a new stage in the development of the technology of plant breeding. With these improved characteristics may occur at the level of individual genes and individual genes that determine a specific trait, can be identified. They may be the final selection, they can be isolated, insert, delete, or modify the genotype or variety. Goal. Identify the features of the manifestation of economically valuable features and decorative properties of Callistephus chinensis and the inclusion of the best varieties in the biotech link, their adaptation to the conditions of the Forest-Steppe of Ukraine and their further use in landscaping. Methods. Laboratory – determination of seed germination; mathematical and statistical - for processing the reliability of the obtained research results. Results. The nutrient medium for growing plant tissues and cells, by analogy with the medium for culturing animal tissues, should contain all that the tissues in the plant organism receive from xylem and phloem currents of substances. However, in practice it has been found that vegetable juices cannot serve as a complete nutrient medium for growing isolated tissues and cells. This manifests the specificity of the receipt, transportation and especially the redistribution of nutrients in the plant. Based on the analysis, research was conducted to study the possibility of mass off-season vegetative propagation of plants of Callistephus chinensis in vitro. Practical recommendations on the selection of sterilizer, sterilization, nutrient medium and for the adaptation period of the best genotypes of this culture have been developed. As a result of the conducted researches the methods of selection of the initial plant material of Callistephus chinensis (Callistephus Chinensis (L.) NEES) and its surface sterilization, modification of existing aseptic culture methods have been studied and mastered. The morphogenetic potential of explants from different plant organs was investigated and selection of nutrient medium and study of the influence of plant growth regulators and physical parameters on the process of morphogenesis was carried out. The features of regeneration of isolated explants depending on the composition of the nutrient medium and selection of conditions for obtaining self-clones of Callistephus chinensis (Callistephus Chinensis (L.) NEES) were studied.